Ethnomathematics-Based Contextual Learning with Interactive Media to Improve Mathematics Problem Solving - Aulia, Fikri; Dianti, Setia Putri; Utami, Wikan Budi; Sina, Ibnu (FKIP Universitas Lampung, 2019)
The aim of the research are determine different math problem solving skills and character of the love’s local culture between the student who receives contextual learning based on ethnomathematics using media interactive as well as students who only use contextual learning. The population of this research is the eighth-grade students in SMPN 9 Tegal city. With the Cluster Random Sampling, get two classes were taken as the experimental group consist56 student into contextual learning based on ethnomathematics with interactive animation and two classes were taken as a control group consist 55 student that only used contextual learning. In the data collecting technique used documentations, tests, and questionnaires. In the analyzing of the data used ano-way manova test. The results of the study showed λcalculated = 0.7925 (λtable = 0.9413). This value indicated that an average value of math problem solving ability and the average questionnaire value of the love in the local culture students experiment class better than the control class students. This result conclude that the ability to math problem solving skills and character of love’s local culture between the experiment class and the control class there are differences.Keywords: contextual learning, ethnomathematics, media interactive, mathematic problem solving. DOI: http://dx.doi.org/10.23960/jpmipa/v20i2.pp39-45